Inflammation, HIV, and Immune Quiescence: Leveraging on Immunomodulatory Products to Reduce HIV Susceptibility. (27th October 2020) - Cromarty, Ross; Archary, Derseree
Abstract : The relationship between inflammation and HIV has been a focus of research over the last decade. In HIV-infected individuals, increased HIV-associated immune activation significantly correlated to disease progression. While genital inflammation (GI) has been shown to significantly increase the risk of HIV acquisition and transmission, immune correlates for reduced risk remain limited. In certain HIV-exposed seronegative individuals, an immune quiescent phenotype characterized reduced risk. Immune quiescence is defined by specific, targeted, highly regulated immune responses that hinder overt inflammation or immune activation. Targeted management of inflammation, therefore, is a plausible strategy to mitigate HIV risk and slow disease progression. Nonsteroidal anti-inflammatory drugs (NSAIDs) such as hydroxychloroquine and aspirin have shown encouraging preliminary results in low-risk women by reducing systemic and genital immune activation. A topical NSAID, containing ibuprofen, is effective in treating vulvovaginal inflammation. Additionally, the glucocorticoids (GCs), prednisolone, and dexamethasone are used to treat HIV-associated immune activation. Collectively, these data inform on immune-modulating drugs to reduce HIV risk. However, the prolonged use of these pharmaceutical drugs is associated with adverse effects, both systemically and to a lesser extent topically. Natural products with their reduced side effects coupled with anti-inflammatory properties render them viable options. Lactic acid (LA) has immunomodulatory properties. LA regulates the genital microbiome by facilitating the growth of Lactobacillus species, while simultaneously limiting bacterial species that cause microbial dysbiosis and GI. Glycerol monolaurate, besides being anti-inflammatory, also inhibited SIV infections in rhesus macaques. The proposed pharmaceutical and natural products could be used in combination with either antiretrovirals for treatment or preexposure prophylaxis for HIV prevention. This review provides a summary on the associations between inflammation, HIV risk, and disease progression. Furthermore, we use the knowledge from immune quiescence to exploit the use of pharmaceutical and natural products as strategic interventions to manage inflammation, toward mitigating HIV infections.